Effect of natural ingredients on the structural-mechanical and physicochemical properties of ice cream mixes - Sapiga, Victoria; Polishchuk, Galyna; Tomczynska-Mleko, Marta; Mleko, Stanislaw; Terpiłowski, Konrad; Pérez-Huertas, Salvador (My University, 2022)
In modern nutrition, there is an increased consumer demand for low-calorie products. Meanwhile, ice cream of classic types is a product with a high fat content (10–16%). Therefore, there is a high demand on production of new types of low-fat or non-fat ice cream. An ice cream is treated as a low-fat product when it contains below 5% of fat. In the process of modifying ice cream recipes, the main task is to obtain a product with a characteristic creamy consistency and high resistance to melting, which is ensured by maintaining a certain balance between the content of free and bound water, the specified values of the cryoscopic temperature and other physicochemical parameters.
Keywords: ice cream; β-glucan; pectin; viscosity; water activity; surface tension; морозиво; β-глюкан; пектин; в'язкість; активність води; поверхневий натяг; кафедра технології молока і молочних продуктів